The navel of the demoness: Tibetan Buddhism and civil religion in highland Nepal - Ramble, Charles (Oxford University Press, 2008)
The people of Mustang and their history -- Inside the Shöyul -- Neighbours and enemies -- From clans to households in Te -- The encounter with Buddhism -- The wild gods of Te -- Buddhists or pagans? -- Agedness of error -- Community law: the creation of a collectivity -- The headmen of Te and the heaven-appointed king --The disenchantment of Te?